Disparities in the Effects of Acuity Circle–based Liver Allocation on Waitlist and Transplant Practice Between Centers. Issue 10 (26th September 2022) - Nagai, Shunji; Ivanics, Tommy; Kitajima, Toshihiro; Shimada, Shingo; Shamaa, Tayseer M.; Collins, Kelly; Rizzari, Michael; Yoshida, Atsushi; Moonka, Dilip; Abouljoud, Marwan
Abstract : Background: Liver allocation in the United States was updated on February 4, 2020, by introducing the acuity circle (AC)–based model. This study evaluated the early effects of the AC-based allocation on waitlist outcomes. Methods: Adult liver transplant (LT) candidates listed between January 1, 2019, and September 30, 2021, were assessed. Two periods were defined according to listing date (pre- and post-AC), and 90-d waitlist outcomes were compared. Median transplant Model for End-stage Liver Disease (MELD) score of each transplant center was calculated, with centers categorized as low- (<25 percentile), mid- (25–75 percentile), and high-MELD (>75 percentile) centers. Results: A total of 12 421 and 17 078 LT candidates in the pre- and post-AC eras were identified. Overall, the post-AC era was associated with higher cause-specific 90-d hazards of transplant (csHR, 1.32; 95% confidence interval [CI], 1.27-1.38; P < 0.001) and waitlist mortality (cause-specific hazard ratio [csHR], 1.20; 95% CI, 1.09-1.32; P < 0.001). The latter effect was primarily driven by high-MELD centers. Low-MELD centers had a higher proportion of donations after circulatory death (DCDs) used. Compared with low-MELD centers, mid-MELD and high-MELD centers had significantly lower cause-specific hazards of DCD-LT in both eras (mid-MELD: csHR, 0.47; 95% CI, 0.38-0.59 in pre-AC and csHR, 0.56; 95% CI, 0.46-0.67 in post-AC and high-MELD: csHR, 0.11; 95% CI, 0.07-0.17 in pre-AC and csHR, 0.14; 95% CI, 0.10-0.20 in post-AC; all P < 0.001). Using a structural Bayesian time-series model, the AC policy was associated with an increase in the actual monthly DCD-LTs in low-, mid-, and high-MELD centers (actual/predicted: low-MELD: 19/16; mid-MELD: 21/14; high-MELD: 4/3), whereas the increase in monthly donation after brain death–LTs were only present in mid- and high-MELD centers. Conclusions: Although AC-based allocation may improve waitlist outcomes, regional variation exists in the drivers of such outcomes between centers.